Entrepreneurship is the best decisions for graduates / Muhammad Firdaus Alias - Alias, Muhammad Firdaus (Faculty of Business and Management, 2017)
The purpose of this study is to determine the relationship factor influences student intention and entrepreneurial intention among degree students of UniversitiTeknologi MARA (UiTM) Malacca City Campus. UiTM Malacca City Campus is one of a three branches campus in Melaka; therefore, it is well known that they have the higher level education students that contribute to their successfulness. This study used the descriptive study to describe the students of UiTM Malacca City Campus. The targeted population is 1773 degree students of UiTM Malacca City Campus and the sample covered 315 respondents from a total population. The sample was selected through simple random sampling techniques. Primary data was collected through the uses of questionnaires. Data analysis have been used in this research study are Descriptive analysis, Reliability testing, Pearson Correlation analysis, and Multiple Regression analysis. Based on the findings of descriptive analysis on the demographic profiles, female student are the highest respondents than male student. Most of them were single degree students with highest ranged 21 to 23 years old. Based on the findings from Pearson Correlation analysis, all independent variables which attitude towards entrepreneurs, perceives support and barrier, and need for achievements are significantly related to entrepreneurial intention. Moreover, attitude towards entrepreneurs is the most related variable related towards entrepreneurial intention. Finally, the most influences factors influencing student intention were attitude towards entrepreneurs with the highest Beta value of 0.573, based on the regression model. The study found out all independent and dependent variables directly related each other. It indicates that the positive factors influencing student intention can give positive impacts towards entrepreneur intention among graduates.